2018
DOI: 10.1016/j.chemosphere.2017.12.131
|View full text |Cite
|
Sign up to set email alerts
|

The domestic fowl (Gallus gallus domesticus) embryo as an alternative for mammalian experiments – Validation of a test method for the detection of endocrine disrupting chemicals

Abstract: In recent decades the embryo of Gallus g. domesticus has been widely used as a model for the study of early sexual development and the potential impact of substances affecting development, including endocrine disrupting chemicals (EDCs). Since there is no standardized procedure available for experiments with the chicken embryo, the objective of our project is to expedite the protocol to assess the potential effects of EDCs on early sexual differentiation. The main aim of the present study was to systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 64 publications
6
30
0
Order By: Relevance
“…The males in the MBP group developed a left ovotestis. Similar results have been obtained with BPA (Berg, Halldin, and Brunström 2001a;Jessl, Scheider, and Oehlmann 2018a). Berg, Halldin, and Brunström (2001a) found that BPA induced ovotestis formation in male chicken embryos as determined histologically at 200 µg/g egg but not at 67 µg/g egg.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The males in the MBP group developed a left ovotestis. Similar results have been obtained with BPA (Berg, Halldin, and Brunström 2001a;Jessl, Scheider, and Oehlmann 2018a). Berg, Halldin, and Brunström (2001a) found that BPA induced ovotestis formation in male chicken embryos as determined histologically at 200 µg/g egg but not at 67 µg/g egg.…”
Section: Discussionsupporting
confidence: 80%
“…All 12 males exposed to 100 µg MBP/g egg in our study developed a left ovotestis, while approximately half of the males developed ovotestis at 200 µg BPA/g egg in the study by Berg, Halldin, and Brunström (2001a). Jessl, Scheider, and Oehlmann (2018a) observed an effect of BPA on cortex thickness already at 75 µg/g egg in both sexes, but there no marked effect on gonad size in males at this dose. These results suggest that MBP is at least as potent as BPA in terms of inducing ovotestis in chicken embryos.…”
Section: Discussionsupporting
confidence: 39%
See 3 more Smart Citations